The Relationship Among Theory of Mind, Comprehensionof Mental Verbs State and Mean Length of Utterance in Children With Hearing Impairment - Zahra Hajgholamrezaee; Fatemeh Hassanati; Pariya Hajgholamrezaee; Akbar Darouie (Journal of Rehabilitation)
Objective The theory of mind is an underlying cognitive ability for the development of social skills, which is closely linked to language development. Since one of the primary deficits resulting from hearing impairment is language difficulty, this study investigates the relationship between theory of mind skills and specific language domains, including mean length of utterance (MLU) as an assessment of grammatical development and comprehension of mental verbs, in 5-7-year-old children with moderate to severe hearing impairment. Materials & Methods This is a descriptive-analytical cross-sectional study. Using the convenience sampling method, 38 children (18 boys and 20 girls) aged 5-7 years with hearing impairments were selected based on the inclusion and exclusion criteria. MLU, theory of mind and comprehension of mental verbs in children were measured using colloquial speech, theory of mind tests and comprehension of mental verb tests, respectively, and the relation between these variables was examined using correlation tests and the effect size assessment. Results The Kolmogorov-Smirnov test showed that the data distribution was normal (P<0.05); therefore, the Pearson correlation coefficient was employed to examine the correlation between variables. The study results revealed no significant relation between MLU and theory of mind (P>0.05). However, a significant relation was found between the comprehension of mental verbs and the theory of mind (P≤0.05). Moreover, a significant relation was also found between MLU and comprehension of mental verbs (P≤0.05). The effect size was calculated using Cohen d, and a value greater than 0.8 was obtained for all correlations, indicating a large effect size. Conclusion There was a significant positive relationship between theory of mind skills and comprehension of mental verbs. Accordingly, enhancing theory of mind skills would be effective in increasing the comprehension of mental verbs. Thus, by creating therapeutic programs based on enhancing theory of mind skills, it may be possible to increase the comprehension of mental verbs and improve advanced expressive language skills in hearing-impaired children. Furthermore, no relationship was observed between the development of the theory of mind and MLU, which is an indicator of grammatical development, suggesting that grammatical development may not be correlated with the development of the theory of mind.